Two new species of Eustigmaeus Berlese (Acari: Trombidiformes: Stigmaeidae) from Brazil, with a key to the American species - Paktinat-Saeij, Saeid; Bagheri, Mohammad; Castro, Tatiane M.m.g. De; Moraes, Gilberto J. De (Zootaxa, 2016)
Two new species of Eustigmaeus, E. piracicabensis Paktinat-Saeij & Bagheri sp. nov., and E. oliveirai Paktinat-Saeij & Bagheri sp. nov., are described based on females collected from soil, humus and moss in the São Paulo state, Brazil. Also, a key to the American Eustigmaeus species is provided.